Application of genetics and genomics to wildlife epidemiology. Issue 4 (2nd April 2016) - Blanchong, Julie A.; Robinson, Stacie J.; Samuel, Michael D.; Foster, Jeffrey T.
ABSTRACT: Wildlife diseases can have significant impacts on wildlife conservation and management. Many of the pathogens that affect wildlife also have important implications for domestic animal and human health. However, management interventions to prevent or control wildlife disease are hampered by uncertainties about the complex interactions between pathogens and free‐ranging wildlife. We often lack crucial knowledge about host ecology, pathogen characteristics, and host–pathogen dynamics. The purpose of this review is to familiarize wildlife biologists and managers with the application of genetic and genomic methodologies for investigating pathogen and host biology to better understand and manage wildlife diseases. The genesis of this review was a symposium at the 2013 annual Wildlife Society Conference. We reviewed the scientific literature and used our personal experiences to identify studies that illustrate the application of genetic and genomic methods to advance our understanding of wildlife epidemiology, focusing on recent research, new techniques, and innovative approaches. Using examples from a variety of pathogen types and a broad array of vertebrate taxa, we describe how genetics and genomics can provide tools to detect and characterize pathogens, uncover routes of disease transmission and spread, shed light on the ways that disease susceptibility is influenced by both host and pathogen attributes, and elucidate the impacts of disease on wildlife populations. Genetic and increasingly genomic methodologies will continue to contribute important insights into pathogen and host biology that will aid efforts to assess and mitigate the impacts of wildlife diseases on global health and conservation of biodiversity. © 2016 The Wildlife Society.